2002
DOI: 10.1117/12.474621
|View full text |Cite
|
Sign up to set email alerts
|

Contamination and degradation of 157-nm stepper optical components: field experience at International SEMATECH

Abstract: Significant improvement in 157nm optical components lifetime is required for successful implementation of pilot and production scale 157nm lithography. To date, most of the 157nm optics lifetime data has been collected in controlled laboratory conditions by introducing predetermined concentrations of contaminants and monitoring degradation in terms of transmission loss. This publication compliments prior work by documenting field experience with the 157nm Exitech Microstepper currently in operation at Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Our results are generally consistent with previous studies that have shown both PAG and deprotection products to be dominant among the species that desorb during resist exposure at 193 nm. , Although quantitative values abound in the literature, comparison of those values to the data reported here is hampered by lack of complete information on resist thickness, light dose, and composition specifics such as identity of polymer and PAG concentration in the previous publications, in addition to some evolution in experimental protocols and accompanying assumptions.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Our results are generally consistent with previous studies that have shown both PAG and deprotection products to be dominant among the species that desorb during resist exposure at 193 nm. , Although quantitative values abound in the literature, comparison of those values to the data reported here is hampered by lack of complete information on resist thickness, light dose, and composition specifics such as identity of polymer and PAG concentration in the previous publications, in addition to some evolution in experimental protocols and accompanying assumptions.…”
Section: Resultssupporting
confidence: 89%
“…If the product flux is sufficient, a film can be formed that alters the lens' optical characteristics. Ever since the first reports of this problem there has been close scrutiny of all materials used inside the tools , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large consortiums have been pivotal towards procuring the resources for tackling the associated technical and financial challenges. SEMATECH has been enabling resist materials research through access to micro exposure tools (MET) for 157 nm, 193 nm immersion, and extreme ultraviolet lithography (EUVL) [16] [17] [18]. Over the past 7 years the current two SEMATECH 0.3 NA EUV METs have been supporting EUV resist materials readiness for a 22/16 nm half-pitch EUV introduction [3] [14] [15].…”
Section: Introductionmentioning
confidence: 99%